BATA BETON (PAVING BLOCK) GEOPOLIMER DENGAN VARIASI KONSENTRASI SERAT SABUT KELAPA - Anni Susilowati; Lauditta Aprilia; Krisno Arif Simanullang (Politeknik Negeri Jakarta, 2016)
ABSTRACT Paving blocks geopolymer concrete is a product of the research material mixture of coarse aggregate (gravel), fine aggregate (sand), fly ash, Na2SiO3 and NaOH. One of the problems is the use of paving blocks or cracks caused by tensile stress and urge that occurs, due to the traffic load exceeds his ability. By adding variety to the mix of coco fiber paving block, is expected to improve on the mechanical properties of the mixture is as strong compressive strength and bending. The aim of this study was to analyze the physical and mechanical properties of geopolymer paving block with coco fiber variations and to obtain optimum levels of coco fiber of compressive strength and flexural strength geopolymer paving block. The method used in this study is the experimental method is to make the test specimens in the form of paving blocks are added coconut coir fiber with a variation of 0%, 0.2%, 0.4%, 0.6% of the weight of the fly ash. With the addition of coconut fiber can decrease the compressive strength of the paving blocks on a variation of 0.2%, down by 7.2% of the variation of 0%. As for the increased variety of coco fiber can improve the flexural strength of paving blocks geopolymer on the variation of 0.2% increased by 37.55% of the variation of 0%. The optimum fiber content on bending strength can not be determined because of the test results obtained value of any variation of coconut fiber is still rising. Keywords: paving block, geopolymer, Coconut Coir Fiber, Compressive Strength, Strong Flexible, Fibre Optimum levels. ABSTRAK Paving block geopolimer merupakan produk dari beton yang merupakan material hasil riset campuran dari agregat kasar (kerikil), agregat halus (pasir), fly ash, Na2SiO3 dan NaOH. Salah satu permasalahan penggunaan paving block adalah terjadinya pecah atau retak yang disebabkan oleh tegangan tarik dan desak yang terjadi, akibat beban lalu lintas melebihi kemampuannya. Dengan menambahkan variasi serat sabut kelapa pada campuran paving block, diharapkan akan meningkatkan terhadap sifat-sifat mekanik campuran tersebut seperti kuat tekan dan kuat lenturnya. Tujuan dari penelitian ini adalah untuk menganalisa sifat fisik dan mekanik paving block geopolimer dengan variasi serat sabut kelapa serta untuk mendapatkan kadar optimum serat sabut kelapa terhadap kuat tekan dan kuat lentur paving block geopolimer. Metode yang dipakai dalam penelitian ini adalah metode eksperimen yaitu dengan membuat benda uji berupa paving block yang ditambahkan serat sabut kelapa dengan variasi 0%, 0,2%, 0,4%, 0,6% dari berat fly ash. Dengan penambahan serat sabut kelapa dapat menurunkan kuat tekan pada paving block pada variasi 0,2% turun sebesar 7,2% dari variasi 0%. Sedangkan untuk penambahan variasi serat sabut kelapa dapat meningkatkan kuat lentur pada paving block geopolimer pada variasi 0,2% naik sebesar 37,55% dari variasi 0%. Kadar serat optimum terhadap kuat lentur belum dapat ditentukan karena dari hasil pengujian yang didapat nilai dari setiap variasi serat sabut kelapa masih terus naik. Kata Kunci: paving block, geopolimer, Serat Sabut Kelapa, Kuat Tekan, Kuat Lentur, Kadar Serat Optimum.